A review of the genus Glyptasida Casey (Coleoptera: Tenebrionidae: Asidini) - Lockwood, Stephanie A.; Pollock, Darren A. (Zootaxa, 2009)
The western American genus Glyptasida Casey is redescribed and reviewed based on structural features of adult specimens. Of 22 available species or subspecies names, three were retained as valid species based on morphological characteristics and statistical analyses of selected measurements: Glyptasida sordida (LeConte), G. aegra (LeConte), and G. rugosissima (Champion). Selected structures of the three species are illustrated and a key separating the species is included. Nineteen names are synonymized as follows: G. sycophanta Casey 1912 [= G. aegra (LeConte 1858)] and the following are synonymized under G. sordida (LeConte 1853): G. costipennis (LeConte 1858), G. aegra irregularis (LeConte 1858), G. interrupta (Champion 1884), G. aegra imperfecta Casey 1912, G. aegra pigra Casey 1912, G. aegra plena Casey 1912, G. costipennis fulvisetis Casey 1912, G. crenicollis Casey 1912, G. heres Casey 1912, G. parvicollis Casey 1912, G. procrustes Casey 1912, G. sordida porcatula Casey 1912, G. stringipennis Casey 1912, G. subpubescens Casey 1912, G. turbulenta Casey 1912, G. turgescens Casey 1912, G. turgescens furtiva Casey 1912, G. turgescens obesa Casey 1912. Lectotypes are designated for G. sordida (LeConte 1853), G. costipennis (LeConte 1858), G. sordida porcatula Casey 1912, G. subpubescens Casey 1912, G. sycophanta Casey 1912, and G. turgescens Casey 1912. Preliminary data on natural history of the genus are presented.